Apollona Korinfskiego wiersze wojenne o Polsce - Orłowski, Jan (Acta Polono-Ruthenica, 2006)
Almost totally forgotten these days Russian poet Apollon Korinfsky (1868-1973) had published main collections of his poems in early XXth century (In the Beams o f a Dream, Under the Burden o f the Cross, Late Flames). He continued epigon tradition of the XIXth century poetry while at the same time in his ballads and poems dealt with heroic past of Russia and other Slavonic nations. Korinfsky can be described as a polonophile. Polish themes and motifs appeared in a series of poems On the Banks o f the Vistula (1908) and in several poems he wrote during WorldWar One (Raise Arms!, Reąuiescant In Pace..., It Shall not Be so, The Battle o f Tannenberg and other).Korinfsky was the champion of the idea of Slav’s brotherhood resulting from fighting by Russia and other Slavonic nations against Germany and Austria. The idea of Polish and Russian reunion was especially appealing to him, because he held it necessary to gain victory in the 1914-1918 war and to establish future relations between Russia and other Slavs. After Russia’s military defeat in 1917, Korinfsky’s idea of Slavonic alliance led by Russia turned out an illusion. Perhaps that is the reason why his poetic work, full of Slavonic motifs, virtually ceased after 1917.